Peningkatan Hasil Belajar Pendidikan Pancasila Menggunakan Model Problem Based Learning (PBL) Berbantuan Media Powtoon di Kelas IV SD Negeri 07 Ikur Koto Kota Padang - Fatiyah, Naila Al; Desyandri, Desyandri (Lembaga Yasin AlSys, 2025)
This research is motivated by the less than optimal implementation of Pancasila Education learning by teachers, so that it has an impact on the low learning outcomes of fourth grade students of SD Negeri 07 Ikur Koto Kota Padang. This study aims to describe the improvement of student learning outcomes through the Problem Based Learning (PBL) model assisted by Powtoon media. This research is a classroom action research (PTK) with a qualitative and quantitative approach, which was carried out in two cycles. Cycle I consisted of two meetings, and cycle II one meeting. Data were obtained from the teaching module assesment, implementation process, and learning outcomes through observation, tests, and non-tests. The results showed improvement in various aspects. The teaching module increased from 81.66 (Good) in cycle I to 96% (Very Good) in cycle II. Teacher activity increased from 78.49% (Good) to 95% (Very Good), while learner activity increased from 78.66% (Good) to 91.66% (Very Good). The learning outcomes of students also increased, with an average score from 73.69 in cycle I to 88.75 in cycle II. Thus, the PBL model assisted by Powtoon media effectively improves student learning outcomes. The implication is that this model can be applied by educators, encourage schools to develop technology-based learning, and support teacher creativity and student motivation. This research also opens up opportunities for further study in other subjects or levels of education.